Pengelolaan Pendidikan bagi Anak Didik Pemasyarakatan: Studi Kasus: Lembaga Pemasyarakatan Kelas II A Salemba-Jakarta Pusat - Eka Rista Harimurti (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
The right to have an education can not be discriminated among children. It is particulary for them who have a problem with the law as the child prisoners. One of The Child Correction Institutions is Lembaga Pemasyarakatan (LAPAS) Klas II A Salemba. As a Child Correction Institutions, LAPAS Klas II A Salemba with the aim of establishing PKBM LAPAS Klas II A Salemba fulfillment of child rights to education. This is in line with the vision and mission of LAPAS Klas II A Salemba is to nurture and educate prisoners and inmates in order to restore the relations with the community by providing a stock of knowledge and skills can be expected to function in a reasonable and able to participate in development. In the implementation of Educational for juvenile, LAPAS Klas II A Salemba use management functions in education, there are (1). Educational Planning. (2). Education Organizing. (3). Education Controlling. All management functions are used by LAPAS Klas II A Salemba for the management of correctional education for juvenile to run well.